PENGARUH KEPERCAYAAN KONSUMEN, KUALITAS PELAYANAN, KUALITAS PRODUK DAN KENYAMANAN NASABAH DALAM BERTRANSAKSI TERHADAP KEPUASAN NASABAHBMT INSAN SADAR USAHA PANGGUNGHARJO, SEWON, BANTUL, YOGYAKARTA - ginanjar ginanjar (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to analyze the influence of consumer confidence, service quality, product quality, and customer convenience in partial transactions on customer satisfaction on BMT Insan Sadar Usaha, Panggungharjo, Sewon, Bantul, Yogyakarata. This research is intended to know the external and internal factors that affect customer satisfaction on BMT Insan Sadar Usaha, Panggungharjo, Sewon, Bantul, Yogyakarata. The population in this study are all customers who have done transactions in BMT Insan Sadar Usaha, Panggungharjo, Sewon, Bantul, Yogyakarata. The sample members in this study amounted to 100 respondents. Accidental sampling technique, accidental sampling is a sample by accident. Customer comfort variables in the transaction does not have a positive and significant impact on customer satisfaction. While consumer confidence variable, service quality and product quality have positive and significant influence to customer satisfaction. The four independent variables affect the customer satisfaction, with the coefficient of determination (adjusted R²) of the four variables is 0.641. This means that customer satisfaction on BMT is influenced by consumer trust, service quality, product quality and customer's convenience in transactions of 64.1%, while the remain ing 35.9% is influenced by other factors.